Menerapkan Prinsip Manajemen yang Baik dalam Pengelolaan Surat : Cara Menciptakan Lingkungan Kerja yang Tertib dan Terorganisir - Harahap, Ulfa Hayana Sari; Farras Fadhilah; Rahmatun Niss; Eka Satya; Tengku Darmansah (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study explores how sound management principles improve document handling for a more organized and efficient workplace. With a structured system, documents are recorded, accessed, and distributed properly. The research uses a qualitative Library Research method, analyzing academic literature and official records related to document administration. Findings show that digitalization and automated systems enhance accuracy and efficiency in document management. Implementing Standard Operating Procedures (SOP) helps maintain order in record-keeping and storage. Additionally, regular evaluations and employee training ensure the system operates effectively. Keywords: document management, digitalization, evaluation